The Influence of Ottoman Empire on the conservation of the architectural heritage in Jerusalem - Ziad M shehada (IAIN Salatiga, 2020)
Jerusalem is one of the oldest cities in the world. It was built by the Canaanites in 3000 B.C., became the first Qiblaof Muslims and is the third holiest shrine after Mecca and Medina. It is believed to be the only sacred city in the world that is considered historically and spiritually significant to Muslims, Christians, and Jews alike. Since its establishment, the city had been subjected to a series of changes as the result of political, economic and social developments that affected the architectural formation through successive periods from the beginning leading up to the Ottoman Era, which then achieved relative stability. The research aims to examine and review the conservation mechanisms of the architectural buildings during the Ottomans rule in Jerusalem for more than 400 years, and how the Ottoman Sultans had contributed in revitalizing and protecting the city from loss and extinction. The researcher followed the historical interpretive method using descriptive analysis based on a literature review and preliminary study to determine Ottoman practices in conserving the historical and architectural heritage of Jerusalem. The research found that the Ottoman efforts towards conserving the architectural heritage in Jerusalem fell into four categories (Renovation, Restoration, Reconstruction and Rehabilitation). The Ottomans focused on the conservation of the existing buildings rather than new construction, because of their respect of local traditions and the holy places.Yerusalem adalah salah satu kota tertua di dunia. Dibangun oleh orang-orang Kanaan pada 3000 SM, kota ini menjadi kiblat pertama umat Islam dan merupakan tempat suci ketiga setelah Mekkah dan Madinah. Kota ini diyakini sebagai satu-satunya kota suci di dunia yang dianggap penting secara historis dan spiritual bagi umat Islam, Kristen, dan Yahudi. Sejak didirikan, kota ini telah mengalami serangkaian perubahan sebagai akibat dari perkembangan politik, ekonomi dan sosial yang memengaruhi pembentukan arsitektur melalui periode-periode berturut-turut dari awal menuju era Ottoman, yang kemudian mencapai stabilitas relatif. Penelitian ini bertujuan untuk menguji dan meninjau mekanisme konservasi bangunan arsitektur selama pemerintahan Ottoman di Yerusalem selama lebih dari 400 tahun, dan bagaimana Sultan Ottoman telah berkontribusi dalam merevitalisasi dan melindungi kota dari kehilangan dan kepunahan. Peneliti mengikuti metode interpretif historis dan analisis deskriptif berdasarkan tinjauan literatur dan studi pendahuluan untuk menentukan praktik Ottoman dalam melestarikan warisan sejarah dan arsitektur Yerusalem. Penelitian ini menemukan bahwa upaya Ottoman ke arah pelestarian warisan arsitektur di Yerusalem jatuh ke dalam empat kategori (Renovasi, Restorasi, Rekonstruksi dan Rehabilitasi). Ottoman berfokus pada konservasi bangunan yang ada daripada konstruksi baru, karena rasa hormat mereka terhadap tradisi lokal dan tempat-tempat suci.